Do post-take ward round proformas improve communication and influence quality of patient care?. Issue 949 (10th November 2004) - Thompson, A G; Jacob, K; Fulton, J; McGavin, C R
Abstract : The post-take ward round is a critical time for reviewing the initial history, examination and results, and the stage at which further treatment and investigations will be determined. However documentation of this ward round is often inadequate, so the benefits of decision making are lost. The documentation of 95 ward rounds was assessed for key items of information before and after the introduction of a proforma sheet. The introduction of the proforma led to a significant improvement in the documentation of a diagnosis, management plan, prophylaxis for deep vein thrombosis, and resuscitation status (p<0.05), which will have a significant impact on patient care.